Intrinsic mechanical vibrations as a missing dimension in amyloid-β clearance: a mechanochemical hypothesis for Alzheimer’s disease - Lai, Xiaochen (Frontiers in Aging Neuroscience, 2026)
Alzheimer’s disease is widely viewed as a disorder of disturbed amyloid-β (Aβ) homeostasis, yet it remains unclear why Aβ shifts from routine turnover to progressive retention and plaque growth in mid-life. This article advances a mechanochemical hypothesis: that age-related reductions in low-intensity mechanical vibrations in the head and neck—arising from everyday self-vocalization (speech, singing, humming) and physiological, non-hypoxic upper-airway motion during stable sleep—contribute to a gradual narrowing of the Aβ clearance bottleneck. Gentle vibrations transmitted through bone and soft tissue could, in principle, enhance interstitial mixing, reduce local supersaturation and nucleation, increase encounter rates at blood–brain barrier and meningeal-lymphatic interfaces, and augment perivascular and glymphatic transport. A sustained decline in this “intrinsic mechanical vibration” (IMV) dose in mid-life might therefore favor Aβ retention without any change in production. We bring together indirect lines of evidence that are compatible with this view, including sleep and glymphatic studies, neuromodulatory stimulation paradigms, music and singing interventions, and hearing-loss epidemiology, and we discuss domains that at first appear inconsistent, such as voice-heavy occupations and obstructive sleep apnea. We then outline a testable cascade that links behavioral and sleep changes in mid-life to reduced mechanical drive and impaired clearance, and we propose concrete experiments spanning human laboratory studies, clinical trials, animal models, and prospective cohorts. Whether ultimately supported or refuted, this IMV–clearance framework highlights mechanical forces as a potentially modifiable dimension of Alzheimer’s disease risk and treatment response, alongside sleep, vascular health, and cognitive engagement.